Strengthening organic fertilizer value chains in Zambia: policy brief - Subakanya, Mitelo; Kasase, Chitundu; Mulungu, Kelvin; Setimela, Peter; Simutowe, Esau; Thierfelder, Christian; Ngoma, Hambulo (CIMMYT, 2025)
The organic fertilizer value chain in Zambia is still at an early stage of development, fragmented, and under-commercialized but holds promise for improving soil health, lowering costs for farmers, and contributing to sustainable agriculture. Key constraints include the exclusion of organic fertilizer from the farmer input support program (FISP), high production and logistics costs, limited farmer knowledge, and limited research and development (R&D). Yet, the abundance of raw materials, emerging private sector players, and regional market opportunities provide a strong foundation for growth if supported by coherent policy reforms, targeted incentives, and strengthened advisory services.